STRATEGI PEMEKARAN KELURAHAN LOA JANAN ILIR DALAM KERANGKA OTONOMI DAERAH - shorea helminasari (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2016)
New paradigm in management of regional governance have experienced of completion and change along with attending of Undang-Undang Number 32 2004 about Governance of Regional, from which orienting power of up at democratization, enableness and society service. This changes also happened in system of regional governance in the form of settlement repeat the areal institute which relate at Peraturan Pemerintah number 8, 2003 about organizational execution guidance of areal peripheral in the place of peraturan pemerintah number 84, 2000. To execute the governance duties is existence of element at regional governance that is subdistrict and of kelurahan as back part of harpoon from regional governance in otonomy execution of direct service and area to society.The purpose this research is knowing and analysing the factors becoming yardstick to be able to conducted by develop Of Kelurahan Loa Janan Ilir, and also know the and analysing the strategy of what has been conducted by Government of Kelurahan Loa Janan Ilir to be Kelurahan  Loa Janan Ilir competent to be develop.This research used the descriptive research method with the inductive approachment and also the technique of data collecting were interview with the respondens and documentation. As for data sources came from governmental officer of Kota Samarinda the resource person is mayor, head of governance section, head of village governance section, head of organization section. At officer of village as resource person that is Lurah, of kelurahan secretary, head of governmental section and staff therewith society circle and supported by the administration data, statistical data, etc.With the existence of otonomy authority of this regional, officer with citizen of society of Kelurahan Loa Janan Ilir to exploit to bloom the  Kelurahan Loa Janan Ilir becomes two new kelurahan with a goal to give the maximum service to the society and also efficiency during and travelled distance to center government because of the distance loa janan ilir. Based on the policy, regional potency, areal to the loa janan ilir requirement, finance ability and availibility of offier resource very suitable if  Kelurahan Loa Janan Ilir was developed in two new of kelurahan and one of main kelurahan.